Control and modeling of active suspension system with load effect [electronic resource ] - 221780 Li, Jingsheng; Yahaya Md. Sam, supervisor (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Elektrik - Mekatronik dan Kawalan Automatik)) - Universiti Teknologi Malaysia, 2007